The Impact of Employer Branding on Commitment to Bank Employees - Ashariana Ashariana (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the relationship between employer branding and organizational commitment to BNI employees in Makassar as many as 100 people using the correlation analysis method. This study found that there was a positive and significant effect of Employer branding on employees' organizational commitment. Employer branding has the greatest influence on affective commitment, amounting to 0.546, then normative commitment of 0.521, then continuous commitment of 0.403. This finding shows that employer branding gives an image to the organization as the best place to work, therefore companies must provide a package of functional, economic, social and psychological benefits by attracting and retaining the best talent of the company. Likewise, employer branding in the banking sector, especially BNI, must continue to be improved so that employee commitment can be maintained. Employees will feel at home and stay with the company because they feel they benefit from the company's various offerings